The impact of distance on post-ICU disability. Issue 4 (July 2022) - D'Arcy, Jack; Haines, Kimberley; Paul, Eldho; Doherty, Zakary; Goodwin, Andrew; Bailey, Michael; Barrett, Jonathan; Bellomo, Rinaldo; Bucknall, Tracey; Gabbe, Belinda J.; Higgins, Alisa M.; Iwashyna, Theodore J.; et al.
Abstract: Background: Nonurban residential living is associated with adverse outcomes for a number of chronic health conditions. However, it is unclear what effect it has amongst survivors of critical illness. Objectives: The purpose of this study is to determine whether patients living greater than 50 km from the treating intensive care unit (ICU) have disability outcomes at 6 months that differ from people living within 50 km. Methods: This was a multicentre, prospective cohort study conducted in five metropolitan ICUs. Participants were adults admitted to the ICU, who received >24 h of mechanical ventilation and survived to hospital discharge. In a secondary analysis of these data, the cohort was dichotomised based on residential distance from the treating ICU: <50 km and ≥50 km. The primary outcome was patient-reported disability using the 12-item World Health Organization's Disability Assessment Schedule (WHODAS 2.0). This was recorded at 6 months after ICU admission by telephone interview. Secondary outcomes included health status as measured by EQ-5D-5L return to work and psychological function as measured by the Hospital Anxiety and Depression Scale (HADS). Multivariable logistic regression was used to assess the association between distance from the ICU and moderate to severe disability, adjusted for potential confounders. Variables included in the multivariable model were deemed to be clinically relevant and had baseline imbalance between groups (p < 0.10). These included marital status and hours of mechanical ventilation. Sensitivity analysis was also conducted using distance in kilometres as a continuous variable. Results: A total of 262 patients were enrolled, and 169 (65%) lived within 50 km of the treating ICU and 93 (35%) lived ≥50 km from the treating ICU (interquartile range [IQR] 10–664 km). There was no difference in patient-reported disability at 6 months between patients living <50 km and those living ≥50 km (WHODAS total disability % [IQR] 10.4 [2.08–25] v 14.6 [2.08–20.8], P = 0.74). There was also no difference between groups for the six major life domains of the WHODAS. There was no difference in rates of anxiety or depression as measured by HADS score (HADS anxiety median [IQR] 4 [1–7] v 3 [1–7], P = 0.60) (HADS depression median [IQR] 3 [1–6] v 3 [1–6], P = 0.62); health status as measured by EQ-5D (mean [SD] 66.7 [20] v 69.8 [22.2], P = 0.24); or health-related unemployment (% (N) 39 [26] v 25 [29.1], P = 0.61). After adjusting for confounders, living ≥50 km from the treating ICU was not associated with increased disability (odds ratio 0.61, 95% confidence interval: 0.33–1.16; P = 0.13) Conclusions: Survivors of intensive care in Victoria, Australia, who live at least 50 km from the treating ICU did not have greater disability than people living less than 50 km at 6 months after discharge. Living 50 km or more from the treating ICU was not associated with disability, nor was it associated with anxiety or depression, health status, or unemployment due to health.